Propolis extract as pulp capping material enhances odontoblast-like cell thickness and type 1 collagen expression (in vivo) - Ira Widjiastuti; Ari Subiyanto; Evri Kusumah Ningtyas; Rendy Popyandra; Michael Golden Kurniawan; Fauziah Diajeng Retnaningsih (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2020)
Background: Propolis is a natural biocompatible material that has been widely studied in dentistry because of its inflammatory, anti-microbial and immunomodulatory properties. One of the active components is caffeic acid phenethyl ester (CAPE). CAPE is effective in stimulating collagen as well as inhibiting the inflammation and degeneration of dental pulp. Purpose: To investigate the post-administration of propolis extract as pulp capping material enhances odontoblast-like cell thickness and type 1 collagen expression in Wistar rats (Rattus Norvegicus) Methods: This research was a true experimental design with a posttest-only control group design. Sixty-three Wistar rats were randomly divided into three groups, with each group consisting of 21 rats: Group I: Positive control; no capping material was administered; Group II: CAPE was administered; Group III: 11% of the propolis extract was administered. All samples were filled with glass ionomer cement. Seven rats from each group were sacrificed after days 7, 14 and 28 of post-pulp capping administration, and their afflicted teeth were subsequently extracted for histologic analysis. Results: No significant difference was seen in odontoblast-like cell thickness after the application of CAPE and propolis on days 7 and 14 (p > 0.05). However, a significant difference was noticed on day 28 (p < 0.05), with the thickness of odontoblast-like cell in CAPE being thinner than that in propolis. A significant difference in the expression of type 1 collagen was observed on days 7, 14 and 28 after the application of the propolis extract compared with CAPE (p < 0.05). Conclusion: The post-administration of propolis extract as a pulp capping material could enhance odontoblast-like cell thickness and type 1 collagen expression in Wistar rats.